EFEKTIVITAS MODEL PEMBELAJARAN SOMATIC AUDITORY VISUALIZATION INTELLECTUALLY (SAVI) TERHADAP HASIL BELAJAR SISWA - Logistya Royyan Ady; Slameto . (JURNAL HANDAYANI PGSD FIP UNIMED, 2017)
Abstract: Effectiveness of Somatic Auditory Visualization Intellectually (SAVI) Learning Model on Student Learning Outcomes. This study aims to determine the effectiveness of the application of Somatic Auditory Visualization Intellectually (SAVI) learning model to the students' mathematics learning outcomes in the 5th grade elementary school mathematics. The subjects of this study were 5th grade students with a total sample of 78 students. Technique used in this research that is, observation and test, then for technique analyze data use test independent sample t-test. The result of data obtained by t-test value can be concluded that there is effectiveness of applying Somatic Auditory Visualization Intellectually (SAVI) learning model toward mathematics learning result in 5th grade students.Keywords : Effectiveness, Somatic Auditory Visualization Intellectually (SAVI) Learning Model, Learning Outcomes, Mathematics Abstrak : Efektivitas Model Pembelajaran Somatic Auditory Visualization Intellectually (SAVI) Terhadap Hasil Belajar Siswa. Penelitian ini bertujuan untuk mengetahui efektivitas dari penerapan model pembelajaran Somatic Auditory Visualization Intellectually (SAVI) terhadap hasil belajar matematika siswa pada mata pelajaran matematika kelas 5 SD. Subjek dari penelitian ini adalah siswa kelas 5 SD dengan jumlah sampel sebanyak 78 siswa. Teknik yang digunakan dalam penelitian ini yaitu, observasi dan tes, kemudian untuk teknik analisis data menggunakan uji independent sample t-test. Hasil dari data yang diperoleh nilai t-test dapat disimpulkan bahwa terdapat keefektivan penerapan model pembelajaran Somatic Auditory Visualization Intellectually (SAVI) terhadap hasil belajar matematika pada siswa kelas 5 SD. Kata Kunci : Efektivitas, Model Pembelajaran Somatic Auditory                     Visualization Intellectually (SAVI), Hasil Belajar,                     Matematika